Comparison of Aerobic and Pilates Exercises on Depression and Sleep Quality in Primigravida Females - Amina Batool, Zoobia Kousar, Mariya Tariq, Maryam Saleem,, Nadia Anwer, Javeria Aslam, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To compare effects of Aerobics and Pilates exercises on depression and sleep quality in primigravida females. Methods: The study was randomized clinical trial and was conducted in children hospital and Mehmooda Hospital Sheikhupura. This study completed in 10 months and convenience sampling technique was used. Total thirty-eight subjects were assigned randomly by using lottery method into two groups. Group A and B received Aerobics and Pilate exercises respectively. Data was collected from all participants at baseline and after 8 weeks of treatment by using CES-D and PSQI questionnaire. After checking the normality of data as p value was greater than 0.05 it was analyzed by using parametric test (independent T test and paired sample T-test) by using SPSS-25. Results: The result of the study showed that in group analysis, improvement in CES-D scale and PSQI were observed in both groups as p value was significant p<0.05.But between the groups significant improvement was seen in CES-D and Quality of Sleep in Pilates training group as p<0.05. Implication: Research on incorporating aerobic exercises during antenatal periods for pregnant women is recommended, with proper follow-up and long-term groupings to ensure treatment efficacy preservation. Conclusion: It was concluded that Aerobics and Pilates exercise training both had significant effects in treating the symptoms of depression and in improving the quality of sleep in antenatal primigravida females. Keywords: Aerobic exercises, Antenatal depression, Pilates exercises, Primigravida females, Sleep quality.